KONSEP FITRAH MANUSIA (Studi Analisis di MTs Darel Fadilah Sidomulyo Pekanbaru) - Ahmad Ghozali (An-Nida', 2018)
Humans have good potential, which includes: physical potential (physical), spiritual (spiritual), and reason (mind). These three potentials will provide the ability for humans to determine and choose their own way of life. Humans are given freedom to determine their destiny. It all depends on how they exploit the potential inherent in him. Spiritual potential in the form of reason. ‘Qald’ and lust. Intellect is thought or ratio and taste can be interpreted with wisdom. Qald is a human nature that can capture all understanding knowledge and wisdom. Lust is a force that drives humans to achieve their desires. The purpose of human life is to worship God Almighty by doing any kind of action as long as it is not prohibited by religion and intentions of worship so that whatever we do is not only beneficial for life in the world but also the interests in the hereafter